Variation of velocity component of ions in a magnetized plasma sheath for different obliqueness of the magnetic field - Adhikari, Bhesha Raj; Basnet, Suresh; Lamichhane, Hari Prasad; Khanal, Raju (Himalayan Physics, 2019)
available with full text.